3D object modeling using AUSTRALIS and RHINOCEROS software - Hashim, K. A.; Setan, Halim; Ahmad, Anuar; Maarof, Ismail (2005)
Most of engineering applications require accurate object measurement using three-dimensional (3D) computer models in order to understand the engineering design of devices and systems. Several measurement techniques are available, such as conventional (using micrometer or tape), geodetic (with total station) and Photogrammetry (especially Digital Close Range Photogrammetry or DCRP). This research focuses on DCRP, which involves object measurement from images taken using digital camera and process by photogrammetric software. This paper demonstrates 3D coordinate measurement performed on the boat model (photographed by Kodak DC290 Digital Camera) using AUSTRALIS Ver.6.0 Photogrammetric software. Based on the 3D coordinates (generated from AUSTRALIS), 3D model is constructed with RHINOCEROS Ver.2.0 (a 3D modeling software).